Serbia Financial Sector Assessment Program Update : Deposit Insurance - International Monetary Fund; World Bank (Washington, DC, 2017)
This note focuses on the deposit insurance scheme. An analysis of the Deposit Insurance Agency (DIA) is provided to the extent that it is relevant to the management of the deposit insurance scheme and no detail analysis of the other functions performed by the DIA, e.g. bank resolution, is included. Policy recommendations on the bank resolution are included in the Aide Memoire. DIA revenue sources are volatile and Deposit Insurance Fund (DIF) related revenues are used to subsidize non-DIF related activities. The legal framework is ambiguous as to whether DIF resources can be used to cover running costs of the DIA. To improve transparency and ensure sustainability of the DIF, the legal framework should be amended to clarify the use of DIF resources and cap use for operating costs. The authorities should develop a medium term strategy for the DIA, including a funding strategy for non-DIF related activities